Effect of gas-chromatography column regeneration during the CHN/S analysis of copper-chromium disulfide - Irina B. Troitskaia; Mikhail M. Syrokvashin; Evgeny V. Korotaev; Anatoly I. Saprykin (Chimica Techno Acta)
The effect of gas-chromatography column (GCC) regeneration during the CHN/S analysis of copper-chromium disulfide CuCrS2 (CCDS) samples on the Euro EA 3000 analyzer was identified. The effect results in a perfect straight baseline on the chromatograms of both CuCrS2 and standard samples. The obtained straight baseline causes high-quality peaks separation. In addition, the reported regeneration procedure reduces significantly the GCC regeneration duration that usually takes up to several days.